2005
DOI: 10.1159/000084135
|View full text |Cite
|
Sign up to set email alerts
|

Another Case of Word-Final Disfluencies

Abstract: It has commonly been thought that stuttering and related disfluencies do not occur at the end of words. However, word-final disfluencies have been documented in the literature and may be underreported at present. This study investigated word-final disfluencies as they occurred in a 12-year-old boy. Word-final disfluencies constituted the major type of disfluencies in this individual and most often involved repetition of a linguistic unit larger than a singleton consonant. They occurred more frequently on conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The children had no history of neurological insult or syndrome, except 1 child in the study by Van Borsel et al [11]. While this child's EWDs were identified after what Van Borsel et al [[11], p. 150] described as a ‘migraine accompagnée', the mother reported that the EWDs had been present for a number of years prior to this episode. Some of the children in these studies were reported to have typical stuttering as well.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…The children had no history of neurological insult or syndrome, except 1 child in the study by Van Borsel et al [11]. While this child's EWDs were identified after what Van Borsel et al [[11], p. 150] described as a ‘migraine accompagnée', the mother reported that the EWDs had been present for a number of years prior to this episode. Some of the children in these studies were reported to have typical stuttering as well.…”
Section: Introductionmentioning
confidence: 82%
“…Details of the children with EWDs in the six extant reports [6,7,8,9,10,11] are shown in table 1, with examples of their EWDs when these could be confirmed. The children had no history of neurological insult or syndrome, except 1 child in the study by Van Borsel et al [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations